Pengaruh Model Pembelajaran PjBL didukung Media Interaktif KeKal (Kearifan Lokal) Terhadap Hasil Belajar Siswa (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This research is motivated by the results of observations made in grade IV of SDN Mojoroto 4. Based on the results of observations. Learning activities that are carried out contextually without using learning media, so that it affects the learning outcomes of students who have not been able to achieve KKTP. The purpose of this study is to determine the influence of the project-based learning model supported by perpetual interactive media on student learning outcomes on local wisdom materials. This research was carried out at SDN Mojoroto 4 grade IV using a Pre-experimental quantitative research method with a one group pretest-posttest design. Sampling was done using a population research sample with a total of 28 students. The data collection technique used in this study is an evaluation question instrument. The results of the data hypothesis test in the pretest posttest using the Paired Samples Test with a significance level of 5% obtained an Asymp.Sig (2-tailed) value of 0.000 ≤ 0.05, so that H0 was rejected. Thus, there is a significant influence on student learning outcomes by using the Project Based Learning learning model supported by KeKal interactive media on local wisdom materials for grade IV students of SDN Mojoroto 4.